Spin-orbit interaction in bremsstrahlung and its effect on the electron motion in a strong Coulomb field - Kovtun, Oleksiy; Tioukine, Valeri; Surzhykov, Andrey; Yerokhin, Vladimir A.; Cederwall, Bo; Tashenov, Stanislav (Physical review. A, Atomic, molecular, and optical physics, 2015)
Linear polarization of bremsstrahlung x rays produced in collisions of longitudinally polarized 2.1-MeV electrons with gold atoms was studied using the Compton scattering technique. We observed that the angle of x-ray polarization is strongly correlated with the incoming electron polarization. This correlation reveals the dominance of the spin-orbit interaction in bremsstrahlung and indicates a striking effect of the electron spin on the electron motion in a strong Coulomb field. The results confirm the validity of the theoretical predictions in a computationally challenging energy regime.